Essential oils in food preservation, flavor and safety - Preedy, Victor R. (Academic Press is an imprint of Elsevier, 2015)
POINTSDISCLAIMER; ACKNOWLEDGMENT; REFERENCES; 3 - Cultivation of Essential Oils; INTRODUCTION; IMPORTANT SPECIES FOR ESSENTIAL OIL CULTIVATION; FACTORS INFLUENCING CULTIVATION OF ESSENTIAL OILS; Environmental Factors; Harvesting-Related Factors; Fertilizers; Cultivars; CULTIVATION OF SELECTED ESSENTIAL OIL-BEARING PLANTS; Turpentine Oil; Peppermint/Mentha Oil; Caraway Oil; Cardamom Oil; Coriander Oil; Ajowan Oil; Dill Oil; Fennel Oil; Orange Peel Oil; Nutmeg Oil; Cinnamon Oil; Garlic Oil; Black Pepper Oil; Vetiver Oil; Rosemary Oil; Palmarosa Oil; Citronella Oil; Clove Oil; Ginger Oil